Efektivitas Edukasi Gizi terhadap Peningkatan Kepatuhan Konsumsi Tablet Fe pada Ibu Hamil : Literature Review - Kurnia Eka Putri; Reni Zuraida; Linda Septiani; Dian Isti Angraini (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
This study aims to analyze the effectiveness of nutrition education in improving adherence to iron tablet consumption among pregnant women through a synthesis of several studies using various educational approaches. The method used was a literature review of six studies with pre-experimental to quasi-experimental designs involving educational interventions through booklets, demonstrations, lectures, digital media, and family-based education. The synthesis results showed that all forms of nutrition education provided significant improvements in knowledge, attitudes, adherence to iron tablet consumption, and, in some studies, physiological improvements in hemoglobin levels and a decrease in the prevalence of anemia. The discussion emphasized that the effectiveness of education is influenced by the depth of the material, delivery method, family involvement, and sustainability of the intervention; a more comprehensive approach tends to produce stronger behavioral changes. In conclusion, nutrition education is a proven effective and essential intervention in improving adherence to iron tablet consumption among pregnant women and supporting efforts to prevent anemia during pregnancy.